Peran Media Pembelajaran Berbasis Teknologi 5.0 dalam Meningkatkan Literasi Digital pada Pembelajaran IPS di Sekolah Dasar - Al Amin; Sutrisno Sutrisno (Asosiasi Peneliti Dan Pengajar Ilmu Sosial Indonesia, 2025)
This study aims to determine the role of technology-based learning media 5.0 in improving digital literacy in social studies learning in elementary schools. The presence of the use of learning media in the digital era 5.0 is a place for skills in the use of technology and information with digital-based media in various areas of life, including in the process of learning activities in schools. The development of digital literacy mastery in learning is expected to be a supporter in developing students' abilities and preparing students who are able to face the demands of the times. The research method used is a qualitative research and development method. This research method was chosen to produce certain products and test the effectiveness of these products. Based on the results of the research and discussion, it can be concluded that in the Era Society 5.0 the role of teachers has shifted with the presence of technology. An interesting learning strategy is needed so that teachers have the role they should. There are five learning strategies that can be applied in Era 5.0, namely helping students learn, providing opportunities for students to develop and excel, strengthening character education, being technologically literate, and becoming effective teachers.